Genetic Studies and Growth Performance of the Yellow Catfish, Mystus Nemurus (Cuv. & Val.) in Thailand - Leesanga, Sanga (2002)
Yellow catfish, Mystus nemurus, was examined to determine levels of genetic subpopulation differentiation among samples of this species obtained from different parts of its range, as well as to compare the genetics of wild and hatchery-bred fish. Horizontal starch gel electrophoresis and histochemical staining techniques were used to examine genetic variation within and among 8 wild and one hatchery populations of M. nemurus in Thailand. Individual specimens were analyzed. at 23 protein-coding loci. Fifteen of the 23 loci examined (65.22 %) were polymorphic. Observed heterozygosities ranged from 0.041 to 0.111. Genetic distance estimates ranged from 0.00510 0.l64. The greatest genetic distance was found between the Chainat and Suratthani populations (0.164), which probably, a level indicative of subspecific differentiation in M. nemurus from within Thailand. Eight wild populations collected from throughout Thailand and a hatchery stock of M. nemurus were also analyzed at the molecular (DNA) level using the technique of RAPD-PCR fingerprinting. Five arbitrary primers were chosen to amplify products which showed 28 polymorphic loci (60.87 %). The highest genetic distance (D) was found between the Chainat and Suratthani populations with a value of 0.289, whereas the lowest was found in the pair of Songkhla population and hatchery stock with a value of 0.087. The dendrogram depicts the genetic relationships among populations of M. nemurus which grouped into four clusters according to their regions of origin namely northern group (Chiengrai and Sukhothai), central group (Kanchanaburi and Chainat), north-eastern group (Nongkhai and Nakormpanom) and southern group (Suratthani, Songkbla and hatchery stock). Horizontal starch gel electrophoresis was applied to differentiate between Mystid and Tachysurid species of catfish : Mystus nemurus, M cavasius, M gulio, Tachysurus caelatus and T. truncatus, collected from the Tapee River, Thailand. Individual fishes were analysed for 22 enzymatic loci. Eleven loci (50.00 %) were found to be polymorphic (P<0.95). The percentage of polymorphic loci ranged from 14.3 % in T. caelatus to 38.1 % in M. nemurus. The highest mean heterozygosity was found in T. truncatus (0. 121±0.048) and the lowest in M cavasius (0.026±0.014). Genetic distance estimates among Mystus species ranged from 0.167 to 0.364 while genetic distance was 0.359 between the two species of Tachysurus. The genetic distance estimates between Mystus and Tachysurus populations ranged from 0.693 to 0.878. Morphometric and meristic variation among two populations from Chainat and Suratthani, which showed the highest genetic distance based on both the isozyme and DNA data, were studied. From the 23 morphometric characters examined, 20 characters showed significant differences. Most characters from the Chainat population differed from the Suratthani population especially for eye diameter (ED) and the distance from the posterior end of the dorsal fin to the anterior end of the adipose fin (DDA), which seemed to be consistent diagnostic characters differentiating the two populations. The relative growth performance of M nemurus collected from northern (Uttaradith), central (Chainat), and southern Thailand (Suratthani) were investigated. Three populations of fish broodstocks were induced to spawn at the same time. The fish larvae were nursed in 0.5 x 2.0 x 0.2 m tanks for 8 weeks. After nursing the fingerlings were separated into 2 groups and cultured at a stocking density of 50 fish/cage in l.0 x 1.0 x 1.5 m floating net cages, in which one group was placed in the north (Lumpang) and another group in the south of Thailand (Suratthani). Fish were fed to satiation with 30 % protein pellets for 48 weeks. At the end of the experiment, the growth performance of fish from both locations (north and south Thailand) were taken and analyzed. The highest growth was found in the population from the south, whereas the lowest growth was found in the central population. The results are in accordance with the values of genetic distances based on both isozyme and RAPD data.